Killer words - Burns, V. M., 1964- (Burns, V. M., 1964- Mystery bookshop mystery, 2021)
"Sam and Nana Jo are back in sleepy North Harbor, Michigan, where Sam is eagerly awaiting the publication of her first book. In search of more immediate excitement, Nana Jo hits the casino with her fellow Shady Acres Retirement Village gal pals--but they get more than they bargained for when they witness Detective Bradley Pitt decking mayoral candidate John Cloverton. As Sam well knows, mystery novels are full of brilliant detectives, genius sleuths, and hero cops. Detective Bradley Pitt--aka "Stinky Pitt"--is another story. In the past, the dull-witted detective has mistakenly accused members of Sam's family for crimes they didn't commit. Now, it's his turn: when Cloverton turns up dead, he's arrested. With his predilection for polyester, Pitt has been wanted by the fashion police for years, but Nana Jo knows her former elementary school math student would never commit murder--it doesn't add up. Somebody's framed the flatfoot to take a fall, and Sam and Nana Jo must step in to restore the reputation and good name of Detective Pitt." --